SPEAKING FACTORS APPROACH TOWARDS THE BUSINESS MOTIVATORS’ SPEECH AT SEMINAR - Ida Hendriyani (Jurnal Syntax Admiration, 2023)
The speech community and the way of speech in which communication is arranged and patterned within it are the main subjects of ethnography of communication. The study aims to analyze business motivators’ speaking factors. SPEAKING involves a variety of factors; including setting, participants, end, act of sequences, key, instrumentality, norm of interaction, and genre. Additionally, this study aims to identify how business motivators or leaders might motivate consultants to manage the firm successfully. Although the consultants are from varied social background, occupations, and ages, they could communicate and work together. In collecting data, the researcher uses some instruments of data collection. They are (1) the sequences of events observation during the seminar, (2) recording the sequences of Seminar event by using video- tape in order to get reliable and accurate data, (3) taking deep interview of seminar participants or members, (4) taking questionnaires to find out participants’ experience during the seminar. In analyzing data, the researcher conducts descriptive analysis through approaching SPEAKING factors (Hymes) in the ethnography of communication. This research uses method of qualitative descriptive analysis. It is used to analyze and describe the event of SPEAKING factors.